Prevalence of caries according to ceod index in 6 years old school children of Cuenca-Ecuador - Bedoya Ocampo, Jessica (2019)
The objective of this study was to evaluate the effect of different surface treatments on the pigmentability of the ceramic after immersion in staining solution. 44 disks of 10 mm radius and 3 mm thickness were made. Samples were randomly assigned among 4 experimental groups (n=11) receiving surface treatment according to the different groups M, H, B, L. (n=10) were distributed for color evaluation and Roughness (RU) and a sample of each group used for scanning electron microscopy (SEM) analysis. For (RU), the data were subjected to ANOVA on ranks (α=0.05), and for the color ANOVA a factor (α=0.05). In the microphotographs of the surface, a qualitative/descriptive analysis was carried out. Results: In the (RU) compared before and after immersion for each group, no statistical difference was observed (p> 0.05). When comparing the types of polish before immersion, a difference was observed between the L group with the other M, H, B (p <0.05). In the analysis of the groups after immersion, there was a difference of group L with B and M (p <0.05). When comparing the color alteration, after immersion, there was a difference between all the ANOVA groups (p <0.05). In the analysis by (SEM) all groups had partially porous surfaces; however, the varnishes produced the best result groups H and B.The texture of the surface is an important factor in the pigmentability of ceramics. the varnished materials showed less color alteration.